LegOSC : mindstroms NXT robotics programming for artists - Cardoso, Jorge (2008)
Robotics is an interesting but difficult area for digital artists who generally don’t have much academic background on electronics or computer programming. Digital art students normally use high-level application to program their visual and sonorous installations. This paper presents LegOSC - a tool that allows the control of the Mindstorms NXT robots from any application that uses the Open Sound Control protocol which is implemented by most of those high-level applications. This allows artists to create works which incorporate robotic parts using the familiar programming environment.